Suppressor screen in Mpl(-/-) mice: c-Myb mutation causes supraphysiological production of platelets in the absence of thrombopoietin signaling - Carpinelli, Marina R. (National Academy of Sciences, 2004)
Genetic screens in lower organisms, particularly those that identify modifiers of preexisting genetic defects, have been used successfully to order components of complex signaling pathways. To date, similar suppressor screens have not been used in vertebrates. To define the molecular pathways regulating platelet production, we have executed a large-scale modifier screen with genetically thrombocytopenic Mpl(-/-) mice by using N-ethyl-N-nitrosourea mutagenesis. Here we show that mutations in the c-Myb gene cause a myeloproliferative syndrome and supraphysiological expansion of megakaryocyte and platelet production in the absence of thrombopoietin signaling. This screen demonstrates the utility of large-scale N-ethyl-N-nitrosourea mutagenesis suppressor screens in mice for the simultaneous discovery and in vivo validation of targets for therapeutic discovery in diseases for which mouse models are available.